Artificial Intelligence and Robotics : Ten Short Lessons - Bentley, Peter J., 1972- (Book collections on Project MUSE., 2020)
"The author explains the world of computer-modeled intelligence for curious general readers. Organized into ten essential lessons, the book covers the historical origins of artificial intelligence and robotics; algorithms for building robots; and the technologies that enable computers to process sensory information, language and communication, and emotion. The book belongs to a new series, Pocket Einstein Series, which features trade titles organized into ten lessons meant to satisfy the curiosity of general readers"--